(3chGTa GdMLHs - (3eMeO UGdM Hf eMeO eMSf GdeGRfOQGfjs
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj cTa GdMLGH Yf HUGFQfG (B... (3GdcTa aj OaY JfGaj GdNdGa aj JYGQV GdCUd hGdXGgQ hGdhaGb Ydi Cf GdabGgI dG JbGhe GdGLJgGOs
(3BNQgG (B:s
(3BNQgG(B: (3hCeG Ydi Gdbhd HXghQg aj LejY eYGfjg adG hdh Yde YOe JMbb GdJHGO ajgeG afbhd YOe GdJHGO HGYJHGQ GdJLhR CcKQ adG jLhR ehVY GdTc HGdZGdHs
(3JHUQI GdYfhGf (B:s
(3PcQ aj GdPQjYI Cfg YOI eLdOGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B18: 115s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3CUhd Gdabgs